Influence of environmental stress toward carotenogenesis regulatory mechanism through in Vitro model system - Othman, Rashidi; Mohd Hassan, Norazian; Mohd Hatta, Farah Ayuni (INTECH, 2017)
Carotenoid biosynthesis is influenced by some aspects and is liable to geometric isomerisation with the existence of oxygen, light, and heat, which affect color degradation and oxidation. The major problems related to carotenoid accumulation inherently originate from pigment instability. This chapter discusses an overview on the influence of stringent control of genetic, developmental, and environmental factors toward carotenoid biogenesis in potato minitubers through the potential model system for rapid initiation, extraction, and analysis of carotenoids. The outcome of this experimental system is a discovery of variables regulating carotenoid accumulation as a result of the environmental change assessment through manipulation of drought stress, light intensity, and nutrient strength on carotenoid accumulation